Perbandingan Pendapatan Usahatani Kelapa Sawit Pola Swadaya Pada Blok A Dan Blok B Desa Bumi Jaya Kecamatan Seruyan Tengah Kabupaten Seruyan Kalimantan Tengah - Rizaldi Imawan; Eko Yuliarsa Sidhi; Tutut Dwi Sutiknjo; Satriya Bayu Aji (JINTAN : Jurnal Ilmiah Pertanian Nasional, 2022)
The agricultural sector is the main sector of the Indonesian economy. As an agricultural country, most of Indonesia’s population depends on the agricultural sector as their livelihood. Therefore, there is a need for national development based on agricultural development. The role of the plantation sector is extensive for increasing farmers’ income and providing raw materials for domestic industry as well as a source of foreign exchange for the country. Oil palm is one of the plantation crops that has an essential role in the plantation sub-sector. The development of oil palm, among others, provides benefits in increasing the income of farmers and the community. This study aimed to determine the income of oil palm farming in Bumi Jaya Village, Seruyan Tengah District, Seruyan Regency. This research was conducted in Bumi Jaya Village, Seruyan Tengah District, Seruyan Regency. The method used in determining the sample in this study was sampling in this purposive sampling method, namely farmers who have a land area of> 5 hectares and planting age between 5-10 years. Data were collected through field research and questionnaires distribution. Data analysis was conducted by calculating total costs, business revenues, business incomes, and feasibility analysis. The results showed that oil palm farming in Bumi Jaya Village, Seruyan Tengah District, Seruyan Regency was profitable because the business provided profits with an NPV value of more than 0 and it was efficient with IRR calculations of 29%.